Urinary cadmium threshold to prevent kidney disease development - Soisungwan Satarug (2018)
© 2018 by the authors. The frequently observed association between kidney toxicity and long-term cadmium (Cd) exposure has long been dismissed and deemed not to be of clinical relevance. However, Cd exposure has now been associated with increased risk of developing chronic kidney disease (CKD). We investigated the link that may exist between kidney Cd toxicity markers and clinical kidney function measure such as estimated glomerular filtration rates (eGFR). We analyzed data from 193 men to 202 women, aged 16-87 years [mean age 48.8 years], who lived in a low- and high-Cd exposure areas in Thailand. The mean (range) urinary Cd level was 5.93 (0.05-57) μg/g creatinine. The mean (range) for estimated GFR was 86.9 (19.6-137.8) mL/min/1.73 m2. Kidney pathology reflected by urinary β2-microglobulin (β2-MG) levels ≥ 300 μg/g creatinine showed an association with 5.32-fold increase in prevalence odds of CKD (p = 0.001), while urinary Cd levels showed an association with a 2.98-fold greater odds of CKD prevalence (p = 0.037). In non-smoking women, Cd in the highest urinary Cd quartile was associated with 18.3 mL/min/1.73 m2lower eGFR value, compared to the lowest quartile (p < 0.001). Evidence for Cd-induced kidney pathology could thus be linked to GFR reduction, and CKD development in Cd-exposed people. These findings may help prioritize efforts to reassess Cd exposure and its impact on population health, given the rising prevalence of CKD globally.